Crosstalk between regulatory non-coding RNAs and oxidative stress in Parkinson’s disease - Zhang, Hantao; Liu, Xiaoyan; Liu, Yi; Liu, Junlin; Gong, Xun; Li, Gang; Tang, Min (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease is the second most common neurodegenerative disease after Alzheimer's disease, which imposes an ever-increasing burden on society. Many studies have indicated that oxidative stress may play an important role in Parkinson’s disease through multiple processes related to dysfunction or loss of neurons. Besides, several subtypes of non-coding RNAs are found to be involved in this neurodegenerative disorder. However, the interplay between oxidative stress and regulatory non-coding RNAs in Parkinson’s disease still remains to be clarified. In this article, we comprehensively survey and overview the role of regulatory ncRNAs in combination with oxidative stress in Parkinson’s disease. The interaction between them is also summarized. We aim to provide readers a relatively novel insight into the pathogenesis of Parkinson’s disease, which would contribute to the development of pre-clinical diagnosis and treatment.